The nature of professional reasoning: An analysis of design in the engineering curriculum - Wolmarans, Nicolette Sarah (School of Education, 2017)
Access to the practice of a profession is controlled by formal education structures. These structures are intended to induct future professionals into the specialised knowledge, skills and values that underpin that profession. Yet, despite meeting the academic requirements of a professional degree, many graduates struggle to 'apply' specialised knowledge when confronted with problems in professional practice. This is a study of the nature of knowledge as it is mobilised in professional reasoning. The case studied was located in engineering education, because knowledge relations tend to be more explicit in education than in practice. The data were collected from design projects located in two differently structured curricula in civil and mechanical engineering curricula. The research questions that directed the study were: 1. What is the nature of the reasoning involved when specialised disciplinary knowledge is recruited to develop specific, often concrete, artefacts? 2. What is the logic of progression in a trajectory of engineering design tasks in terms of the relation between knowledge and artefact? The study draws on two intellectual fields: models of professional reasoning and design thinking on one hand, and social realism in the sociology of education on the other. These traditions take different positions on professional reasoning. Design thinking is concerned with contextual detail and case precedent, while social realism in the sociology of education is concerned with conceptual coherence within knowledge specialisations and the power of generalisation. Both offer important insights into professional reasoning, but alone neither is adequate. The analysis was done using the semantics dimension of Legitimation Code Theory, LCT (Semantics), which required an adaptation in order to fully describe the significance of contextual detail evident in the data. The findings showed that specialised knowledge and contextual detail interact far more dialectically than previously assumed. This provides empirical insights for structuring curricula. Students can be more intentionally inducted into recontextualising academic knowledge for the purpose of solving contextually emergent problems. Theoretically the study contributes to the social realist school within the sociology of education by revealing its blindness to contextual detail and consequently offering a fuller understanding of the nature of regions. This has implications for other studies of professional knowledge and education.